Financial Literacy and its Impact on Investment Decision in Nepalese Share Market - Sharma, Bishnu Maya (Journal of Janta Multiple Campus, 2025)
Financial literacy and investment decision are interrelated terms which have a great significance in the field of finance. This study aims at examining the impact of financial literacy on investment decision with respect to the individual investors of Nepalese share market. Financial literacy has been expressed in four dimensions- personal savings, risk tolerance behavior, investment option and financial knowledge. Two hundred and twenty- one respondents were selected by using convenience sampling method from the Koshi province of Nepal. Quantitative method of data analysis has been employed on primary data collected through structured questionnaires. Pearson correlation coefficient and ordinary least square regression model has been applied for examining the association between financial literacy and investment decision. The result of the analysis showed the positive and significant impact of personal saving, risk tolerance behavior, investment options and financial knowledge on investment decision. This study suggests to increase the level of literacy on financial matters of the individual investor to improve their potentiality in managing and investing funds in complex and everchanging financial environment in order to perform optimum investment decision.